2013
DOI: 10.1186/2050-2974-1-6
|View full text |Cite
|
Sign up to set email alerts
|

I’m not just fat, I’m old: has the study of body image overlooked “old talk”?

Abstract: BackgroundResearch indicates that body dissatisfaction is correlated with and often predictive of both physical and mental health problems. “Fat talk,” a well-studied form of body image talk in adolescents and university-aged women, has been implicated as contributing to body dissatisfaction and mediating the relationship between body dissatisfaction and other mental health problems. Limited research, however, has investigated fat talk across the female lifespan. Further, consistent with most body image resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
85
3
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(101 citation statements)
references
References 38 publications
6
85
3
7
Order By: Relevance
“…Example items include: “When my peers have dessert or ‘junk’ food, they say they are ‘being bad’ or ‘cheating’” and “When my peers haven't exercised in a while, they talk about how ‘lazy’ they are being.” Items were summed to form a total score. In samples of young adult women, the BTS had a large significant correlation ( r = .71, p < .001) with an established measure of fat talk (i.e., Fat Talk Scale [Clarke, Murnen, & Smolak, ] as modified by Becker, Diedrichs, Jankowski, & Werchan, ) and demonstrated good 2‐week test–retest reliability ( r = .76, p < .001) (Karam et al, ). In this study, Cronbach's alpha was .93.…”
Section: Methodsmentioning
confidence: 99%
“…Example items include: “When my peers have dessert or ‘junk’ food, they say they are ‘being bad’ or ‘cheating’” and “When my peers haven't exercised in a while, they talk about how ‘lazy’ they are being.” Items were summed to form a total score. In samples of young adult women, the BTS had a large significant correlation ( r = .71, p < .001) with an established measure of fat talk (i.e., Fat Talk Scale [Clarke, Murnen, & Smolak, ] as modified by Becker, Diedrichs, Jankowski, & Werchan, ) and demonstrated good 2‐week test–retest reliability ( r = .76, p < .001) (Karam et al, ). In this study, Cronbach's alpha was .93.…”
Section: Methodsmentioning
confidence: 99%
“…Becker and colleagues (2013) also examined fat talk in a large (N = 914) international internet sample with women who ranged in age from 18–87. Results indicated that women across the lifespan reported engaging in fat talk and that only women in the oldest cohort (ages 61+) reported significantly less fat talk than the youngest cohort (ages 18–29).…”
Section: Psychosocial Factors Associated With Body Dissatisfaction Inmentioning
confidence: 99%
“…Becker et al (2013) also examined the degree to which participants reported engaging in “old talk.” They defined old talk as speech that implicitly or explicitly reinforces the young component of the thin-young-ideal. Participants ages 46 and older reported engaging in significantly more old talk than the 18–29 year old cohort and the 30–45 year old cohort.…”
Section: Psychosocial Factors Associated With Body Dissatisfaction Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased stress and other emotional issues are associated with menopause and with ageing in general (Becker et al, 2013), and stress can interfere with one's ability to regulate eating habits and find the time to exercise (Lewis & Sutton, 2011). The way one copes with stress depends on several factors, including age, financial status, ethnicity, and gender (Tanyi & Werner, 2007).…”
Section: Introductionmentioning
confidence: 99%